EDUKASI TERHADAP PENGETAHUAN IBU HAMIL TENTANG HIPERTENSI DALAM KEHAMILAN - Kartika, Amelia; Hutabarat, Julietta; Sitorus, Samsider (Poltekkes Kemenkes Medan, 2023)
From North Sumatra Sectoral Statistics data (2021), it is known that from 2018 to 2021 the incidence of hypertension in pregnancy has increased by 25 cases caused by late early detection. This delay is caused by inadequate education and knowledge of pregnant women about hypertension in pregnancy. The purpose of this study was to determine the effect of education on pregnant women's knowledge about hypertension in pregnancy in the working area of the Dalu Sepuluh Health Center. This research is a quasi-experimental study with nonequivalent control group design, examined 46 respondents, obtained through accidental sampling technique, and divided into two groups, 23 respondents in the intervention group and 23 others in the control group, and used a knowledge questionnaire with 20 questions as measuring instrument and then analyzed with the Paired Sampling T-Test. Through research, the results were obtained that: the average knowledge of the intervention group on the first day was 12.82, while on the seventh day it was 15.47 with a mean difference of 2.65 with p-value = 0.000 <0.05, so H1 was accepted; whereas in the control group the average knowledge on the first day was 11.65 while on the seventh day it was 12.91 with a mean difference of 1.26 where p-value = 0.092> 0.05, then H1 was rejected. It is expected that the health workers at the Dalu Sepuluh Health Center will provide education while giving dissemination to increase mothers' knowledge, presented in various media, such as leaflets.